The Myth of Bidadari and the Betrayal of Women: Reading Gender in Islamic Sermons through Barthes’ Semiotics - Febi Komala Dewi; Iklilah Muzayyanah Dini Fajriyah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This study critically examines the symbolic construction of bidadari (heavenly maidens) as eschatological rewards for men, with particular reference to an Islamic sermon delivered by Habib Nabil on the YouTube program Islam Itu Indah, in the episode titled “Laki-Laki Mendapatkan Bidadari, Kalau Perempuan Dapat Apa?”. The sermon presents a gendered vision of paradise that reflects patriarchal interpretations by depicting women as passive rewards associated with male virtue. Such perspectives draw upon essentialist claims of men’s “natural inclination” toward women and have been widely circulated through religious media. Employing Roland Barthes’ semiotic theory alongside postmodern feminist analysis, this research uses qualitative content analysis to unpack the verbal and symbolic messages embedded in the sermon. The findings suggest that the image of bidadari does not derive directly from the Qur’anic text, but has instead been shaped through cultural, historical, and clerical interpretations into a patriarchal myth. This myth can obscure Islam’s egalitarian principles and reinforce gendered norms that position women in subordinate roles both theologically and socially. By deconstructing the bidadari narrative as a second-order myth, the study demonstrates how religious symbols may function hegemonically while concealing their socio-historical origins. It calls for a re-reading of Islamic eschatology that foregrounds ‘adl (justice) and karamah (dignity) as central ethical values, affirming the equal spiritual agency of both men and women in the afterlife. Ultimately, this research contributes to ongoing efforts in developing gender-sensitive approaches within Islamic hermeneutics.